Calculation of Liquidity, Solvency and Profitability Ratio in Manufacturing Company - Rally Ferry Agusta; Shinta Wahyu Hati (Journal of Applied Accounting and Taxation, 2018)
This research discuss the calculation of liquidity, solvency and profitability ratios. The liquidity ratio is the ratio that describes the company's ability to meet short-term liabilities, solvency ratio is the ratio that describes the company's ability to meet long-term obligations and the profitability ratio is the ratio that measures the company's ability to generate profits. The aim of this final project is to find out the company's financial condition. The collection of data was used secondary techniques of data in the form of statement of financial position and income statement. The method of analysis used on this study is descriptive analysis method is done by creating a picture and interpret the data relating to fact, circumstances, variable and ongoing events at the time of study. The results obtained after performing the calculation of liquidity, solvency and profitability ratios is the condition of the company based on the liquidity and solvency ratios is in proper and healthy, meanwhile the company is in bad condition based on profitability ratio’s view.